Muslim Americans in the Military: Centuries of Service By Edward E. Curtis IV (Bloomington: Indiana University Press, 2016. 102 pages.) (American Journal of Islam and Society, 2018)
Edward E. Curtis IV is one of the most important scholars of Islam in theUnited States. This slim volume is a welcome addition to his work, andshould be required reading for all who are interested in the place of Muslimswithin the history of America. One also wishes that the book be readwidely by American Muslims. As the latter day prophet, Bob Marley, oncesang about other soldiers in the Americas, “If you know your history/ Then you would know where you’re coming from.” Curtis’ book helps us, asAmerican Muslims, to learn about our own history in our country.The book is not written for a specialized audience, and could easily beused by undergraduate or even senior high school students in a number ofcourses on Islam or religion in America. It is a very short volume, comingin at 82 pages of text with a single additional page of notes. The book is dividedinto five chapters of roughly equal length. The first chapter introducesthe contemporary issues of American Muslim soldiers in the United Statesarmed forces through the stories of Captain Humayun Khan and CorporalKareem Rashad Sultan Khan. Corporal Khan became widely known whena photo of his mother, Elsheba, cradling his gravestone was mentioned byGeneral Colin Powell in the 2008 election. Captain Khan’s introduction tothe American public was more recent, when his father, Khizr, spoke abouthis son’s sacrifice on the final night of the Democratic National Conventionin 2016 ...